Enhancing Company Value Through Profitability Mediation (A Study on Manufacturing Companies Listed on The Indonesia Stock Exchange During The Period of 2018-2021) - Erisa Aprilia Wicaksari; Endah Prapti Lestari; Nadia Ingrida Kusumadewi (Management Analysis Journal, 2023)
The research is based on the fact that there is a significant fluctuation in the performance of companies listed on the Indonesia Stock Exchange, leading to the emergence of a phenomenon known as the 'gap' phenomenon. The gap phenomenon is characterized by the inconsistency in the influence of variables such as ROE, capital expenditure, and tangible assets on profitability and their impact on company value. The objective of this study is to analyze the influence of the variables ROE, capital expenditure, and tangible assets on profitability and their impact on company value in the manufacturing industry listed on the IDX during the period from 2018 to 2021. The population in this study consists of all manufacturing companies listed on the Indonesia Stock Exchange during the period from 2018 to 2021. The research analysis method used in this study is Smart PLS.